Peran Komisi Penyiaran Indonesia Daerah (KPID) Jawa Timur Dalam Mewujudkan Good Governance di Sektor Penyiaran - Muhammad Faqih (Indonesian Journal of Humanities and Social Sciences, 2024)
The purpose of this research is to deeply analyze the role of East Java Regional Indonesian Broadcasting Commission (KPID) in creating transparent, efficient, accountable, equitable, and participatory governance. The method used in the research is empirical juridical research method with several approaches including 1. statutory approach; 2. case approach; 3. conceptual approach; and 4. comparative approach. The results of the research on the role of KPID East Java in realizing good governance in the broadcasting sector include; 1) Enforcing broadcast content control in East Java in accordance with applicable laws and regulations; 2) Realizing broadcasts that are educative and informative and have locality value; 3) Realizing healthy, smart and quality broadcast programs that are beneficial for the welfare of the people of East Java; 4) Optimizing KPID East Java Cooperation with Stakeholders; 5) Encouraging Digitalization and Convergence of Broadcasting Institutions in East Java; 6) Developing Human Resources Capacity in the field of Broadcasting.